2022
DOI: 10.3389/fnins.2022.937906
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome-Linked Metabolites in the Pathobiology of Major Depression With or Without Anxiety—A Role for Bile Acids

Abstract: BackgroundThe gut microbiome may play a role in the pathogenesis of neuropsychiatric diseases including major depressive disorder (MDD). Bile acids (BAs) are steroid acids that are synthesized in the liver from cholesterol and further processed by gut-bacterial enzymes, thus requiring both human and gut microbiome enzymatic processes in their metabolism. BAs participate in a range of important host functions such as lipid transport and metabolism, cellular signaling and regulation of energy homeostasis. BAs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 83 publications
1
17
0
Order By: Relevance
“…The intestine, also known as the second brain, has a close connection with the brain [ 55 ]. Tremendous progress has been made in studying the bidirectional interactions between the gastrointestinal tract and the central nervous system [ 56 ], and understanding the interaction between the digestive system with the brain may provide novel approaches for prevention and treatment of MDD [ 57 , 58 ].…”
Section: Monoamine In the Digestive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestine, also known as the second brain, has a close connection with the brain [ 55 ]. Tremendous progress has been made in studying the bidirectional interactions between the gastrointestinal tract and the central nervous system [ 56 ], and understanding the interaction between the digestive system with the brain may provide novel approaches for prevention and treatment of MDD [ 57 , 58 ].…”
Section: Monoamine In the Digestive Systemmentioning
confidence: 99%
“…Recently, it has been found that patients with MDD had a significantly higher prevalence and incidence of chronic liver disease than the general population [ 74 ]; thus, the integrative activity of liver and brain might play a role in depression [ 59 , 60 ]. Part of the reason might be due to the metabolites, such as the bile acids [ 55 ]. Bile acids are steroid acids which are synthesized in the liver and further processed in the gut by digestive enzymes.…”
Section: Monoamine In the Digestive Systemmentioning
confidence: 99%
“…Bile acids (BA) can independently modulate the function and effects of the brain ( Nunes et al, 2012 ; Bazzari et al, 2019 ), gut ( Zhou et al, 2020 ), and gut microbiome ( van Best et al, 2020 ), while each of these layers of the brain-gut-microbiome axis may contribute to the overall outcome in the brain ( Garcia et al, 2022 ; Lirong et al, 2022 ; MahmoudianDehkordi et al, 2022 ; Qu et al, 2022 ). Hence, there is a large spectrum and significant complexity in how BA and the intestinal flora affect brain function.…”
Section: Discussionmentioning
confidence: 99%
“…According to researchers' speculation, acupuncture restored gut flora balance primarily by regulating glycerophospholipid metabolism and primary bile acid biosynthesis. Several studies have shown that intestinal microflora is involved in the pathogenesis of depression 10.3389/fnins.2023.1146946 through glycerophospholipid metabolism and primary bile acid biosynthesis (Gong et al, 2021;MahmoudianDehkordi et al, 2022). Accordingly, it can be speculated that electroacupuncture might be useful in treating depression by regulating intestinal flora's production of glycerophospholipids and bile acids.…”
Section: Effect On Metabolites and Metabolic Pathwaysmentioning
confidence: 99%